Resolution of the Interregional Scientific and Practical Conference "Education and a teacher in the 21st century: challenges and prospects” (November, 11-13 2010, Kyzyl) - ., . . (The New Research of Tuva, 2011)
Resolution of the Interregional Scientific and Practical Conference "Education and a teacher  in the 21st century: challenges  and prospects” (November, 11-13 2010, Kyzyl)
Keywords: conference-2010; resolution; education; Tuva